Women’s Ordination in Judaism: A British-European Perspective - Sarah, Elli Tikvah (Women in Judaism, 2024)
In this article, while focusing on the ordination of women rabbis in the British-European context, the author acknowledges the phenomenon of non-ordained female religious leaders in the late nineteenth and early twentieth centuries, surveys the development of women's ordination in the United States, and includes the more recent development of orthodox women receiving s’mikhah in the United States and in Israel. Towards the end, she reflects on the question, ‘Are women rabbis making a difference?’